(untitled) (Fiep Bulletin - online, 2014)
Introduction: In 2007 between February and July recreational activities had been carried out under the Project called Life in Movement. The project’s aimed public is severely mentally disturbed individuals. Three factors are pointed out in the specialized literature as characteristics of the individuals suffering from psychosis: concrete thought, sedentary lifestyle and difficulty in establishing and maintaining social relationship. (BORGES, 2005; FAULKNER e TAYLOR, 2005). Objective: Offer opportunities to develop social relationship in group of mentally disturbed individuals by recreation activity. Methodology: Qualitative study, using the following instruments: systemized observations of the participants during their period at Laboratory of Movement; interviews with participants, relatives and reference professionals; participant Frequency File. Results: Specific modifications had been showed in motor, psychics and social competencies, which lead to social bond formation among the participants. Conclusion: By this study, it’s possible to confirm that with the recreational activities offered by the project and with the methodology used in the study social relationship was developed in this group of severely mentally disturbed individuals. The social relationship arose based on the motor, psychic and social participants competencies modifications.